Banking globalization, local lending, and labor market effects: Micro-level evidence from Brazil - Felix Noth; Matias Ossandon Busch (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2019)
Little is known about how banks' domestic funding networks affect the transmission of capital flows reversals to the real economy. Our robust results show that a foreign funding shock to banks in Brazil negatively affects lending by their regional branches, especially when they are subjected to funding fragmentation. This effect triggers a sizable drop in credit and job creation at the municipal level. Our findings suggest that despite substitution possibilities across banks and firms, banks' funding networks matter to explain the distributional effects of foreign financial shocks.
urn:nbn:de:gbv:3:2-112341
Keywords: E24; E44; G01; G21; 330; capital flows reversals; branch funding networks; bank lending; regional labor markets